Population‐based study on resection rates and survival in patients with colorectal liver metastasis in Norway. Issue 5 (9th February 2017) - Angelsen, J.‐H.; Horn, A.; Sorbye, H.; Eide, G. E.; Løes, I. M.; Viste, A.
Abstract: Background: Detailed knowledge about the proportion of patients with colorectal liver metastases (CLM) undergoing resection is sparse. The aim of this study was to analyse cumulative resection rates and survival in patients with CLM. Methods: For this population‐based study of patients developing CLM during 2011–2013, data were extracted from the Norwegian Patient Registry and the Cancer Registry of Norway. Results: A total of 2960 patients had CLM; their median overall survival was 10·9 months. Liver resection was performed in 538 patients. The cumulative resection rate was 20·0 per cent. The cumulative resection rate was 23·3 per cent in patients aged less than 40 years, 31·1 per cent in patients aged 40–59 years, 24·7 per cent in those aged 60–74 years, 17·9 per cent in those aged 75–79 years and 4·7 per cent in patients aged 80 years or more ( P < 0·001). In multivariable analysis, resection rate was associated with age, extrahepatic metastases, disease‐free interval and geographical region. Overall survival after diagnosis of CLM was affected by liver resection (hazard ratio (HR) 0·54, 95 per cent c.i. 0·34 to 0·86), rectal cancer (HR 0·82, 0·74 to 0·90), metachronous disease (HR 0·66, 0·60 to 0·74), increasing age (HR 1·32, 1·28 to 1·37), region, and extrahepatic metastases (HR 1·90, 1·74 to 2·07). Three‐ and 4‐year overall survival rates after hepatectomy were 73·2 and 54·8 per cent respectively. Conclusion: The cumulative resection rate in patients with CLM in Norway between 2011 and 2013 was 20 per cent. Resection rates varied across geographical regions, and with patient and disease characteristics. Abstract : Variation among patients and regions